Therapeutic Effect of Antioxidant Extract of Ocimum Gratissimum on Liver Toxicity Model in Rats - Muhammad Shahid Javed, Sohail Iqbal, Nida Qasim Hayat, Attya Zaheer, Fatima Qaiser, Faiza Irshad, Amal Shaukat, (Pakistan Journal of Medical & Health Sciences, 2022)
Background:Lead harms haematological, biochemical, and hepatic parameters, hence studies have concentrated on antioxidants with therapeutic potentials. Objective: Induced hepatotoxicity and hemato-biochemical parameters in adult Wistar rats with Ocimum Gratissimum extract. Methodology: 42 adult Wistar rats were divided into seven groups of five. Group A was the control, Group B had 120 mg/kg lead, and Group C got 300 mg/kg OG. D and E had 120 mg/kg lead before 300 mg/kg and 600 mg/kg OG. Group F had 300 mg OG extract, then 120 mg lead, whereas Group G got 120 mg lead and 1000 mg ascorbic acid. The animals were then slaughtered and blood and liver tissues were taken for biochemical and histological investigation. Results: The outcome revealed a rise in Control but a drop in B. ALT, AST, GGT, and ALP levels were higher in Group B than in Control and other treatment groups (p≤ 0.05). As in Groups D, E, F, and G, histological investigation of liver tissues revealed degenerative alterations with localised necrosis and aggregated inflammatory cells in B. Conclusion: The extract of OG has the potential to be employed as a medicinal agent in the treatment of lead poisoning.